-72=-9(-6+1m)

Simple and best practice solution for -72=-9(-6+1m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -72=-9(-6+1m) equation:


Simplifying
-72 = -9(-6 + 1m)
-72 = (-6 * -9 + 1m * -9)
-72 = (54 + -9m)

Solving
-72 = 54 + -9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9m' to each side of the equation.
-72 + 9m = 54 + -9m + 9m

Combine like terms: -9m + 9m = 0
-72 + 9m = 54 + 0
-72 + 9m = 54

Add '72' to each side of the equation.
-72 + 72 + 9m = 54 + 72

Combine like terms: -72 + 72 = 0
0 + 9m = 54 + 72
9m = 54 + 72

Combine like terms: 54 + 72 = 126
9m = 126

Divide each side by '9'.
m = 14

Simplifying
m = 14

See similar equations:

| (15x-13)+(8x+29)+(2y)=180 | | 80-3x=14 | | 7(4x-2)= | | 5u+14=49 | | 15/33=m/22 | | -5m(-4+9m)-2m(4+5m)= | | 5x-6=4x-89 | | 31-4x=59 | | 7=2y-17 | | 4x+1=3y+5 | | 120-45=75/15 | | 4a-7=4(a-2x)+3 | | -20=1b-15 | | -3(3x+1)+2x-2=-54 | | y=70[2(x-4)] | | 4j+5j+-8j+-18j+11j=18 | | (1/2)^4 | | -18=4v+6 | | 27=7+1x | | x^2+11x+29=x+4 | | (7x+5)+(9x-13)+(4y)=180 | | x^3-30x+144x+256=0 | | 2.00=.15x+2.75 | | 4/3=8x | | r+13=-4 | | 1=2w-31 | | 12.58=-8(8m+5)-3(-m+8) | | 6x+1+5=4x-2 | | y=5(x+3)-20 | | x^3-30x^2+400=0 | | 4p+3p=0 | | 3/4x3/1 |

Equations solver categories